2022
DOI: 10.3390/molecules27217390
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethanoid and Phenylmethanoid Glycosides from the Leaves of Ligustrum robustum and Their Bioactivities

Abstract: The phytochemical study on the leaves of Ligustrum robustum, which have been used as Ku-Ding-Cha, led to the isolation and identification of three new phenylethanoid glycosides and three new phenylmethanoid glycosides, named ligurobustosides R1 (1b), R2–3 (2), R4 (3), S1 (4b), S2 (5), and S3 (6), and five reported phenylethanoid glycosides (7–11). In the bioactivity test, (Z)-osmanthuside B6 (11) displayed strong fatty acid synthase (FAS) inhibitory activity (IC50: 4.55 ± 0.35 μM) as the positive control orlis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, among the harmful effects of fatigue, oxidative stress and inflammation have also been observed [ 60 ]. Our findings enable deeper insight into the therapeutic potential of alternating the BALF microbiota, especially Vibrio , to alleviate fatigue in patients with silicosis [ 61 63 ]. However, the relationship between BALF Vibrio , fatigue, and haemoglobin remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among the harmful effects of fatigue, oxidative stress and inflammation have also been observed [ 60 ]. Our findings enable deeper insight into the therapeutic potential of alternating the BALF microbiota, especially Vibrio , to alleviate fatigue in patients with silicosis [ 61 63 ]. However, the relationship between BALF Vibrio , fatigue, and haemoglobin remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous phytochemical studies [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], about 90 chemical constituents, including trans - p -hydroxycinnamic acid, 34 trans - p -hydroxycinnamic acid esters ( Figure 1 ), flavonoid glycosides, lignan glycosides, and other compositions, were isolated and identified from the leaves of L. robustum .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous biological investigations [ 14 , 15 , 16 , 17 ], the chemical compositions isolated from the leaves of L. robustum were tested, and the results showed that (1) trans - p -hydroxycinnamic acid displayed stronger α -glucosidase inhibitory activity than the positive control acarbose; (2) trans - p -hydroxycinnamic acid and several trans - p -hydroxycinnamic acid esters displayed no weaker fatty acid synthase (FAS) inhibitory activities than the positive control orlistat; (3) trans - p -hydroxycinnamic acid and a lot of trans - p -hydroxycinnamic acid esters revealed stronger 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) ammonium salt (ABTS) radical scavenging effects than the positive control L-(+)-ascorbic acid and revealed moderate α-amylase inhibitory activities. What is more, trans - p -hydroxycinnamic acid esters might be hydrolyzed with catalysis of carboxylesterase or gastric acid in vivo [ 18 , 19 ] and release trans - p -hydroxycinnamic acid, meaning that trans - p -hydroxycinnamic acid esters are the prodrugs of trans - p -hydroxycinnamic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous phytochemical studies [2,[5][6][7][8][9][10][11][12][13][14][15][16][17], about 90 chemical constituents, including transp-hydroxycinnamic acid, 34 trans-p-hydroxycinnamic acid esters (Figure 1), flavonoid glycosides, lignan glycosides, and other compositions, were isolated and identified from the leaves of L. robustum. In our previous biological investigations [ [14][15][16][17], the chemical compositions isolated from the leaves of L. robustum were tested and the results showed that: (1) trans-p-hydroxycinnamic acid displayed stronger α-glucosidase inhibitory activity than the positive control acarbose; (2) trans-phydroxycinnamic acid and several trans-p-hydroxycinnamic acid esters displayed no weaker fatty acid synthase (FAS) inhibitory activities than the positive control orlistat; (3) trans-phydroxycinnamic acid and a lot of trans-p-hydroxycinnamic acid esters revealed stronger 2,2'-azinobis(3-ethylbenzthiazoline-6-sulphonic acid) ammonium salt (ABTS) radical scavenging effects than the positive control L-(+)-ascorbic acid, and revealed moderate α-amylase inhibitory activities. What is more, trans-p-hydroxycinnamic acid esters might be hydrolyzed with catalysis of carboxylesterase or gastric acid in vivo [18,19], and release trans-p-hydroxycinnamic acid, meaning that trans-phydroxycinnamic acid esters are the prodrugs of trans-p-hydroxycinnamic acid.…”
Section: Introductionmentioning
confidence: 99%